2013
DOI: 10.1111/jnc.12527
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin B: intra‐ and extra‐cellular mechanisms to regulate catecholamine storage and release, in catecholaminergic cells and organisms

Abstract: CHGB is the major matrix protein in human catecholamine storage vesicles. CHGB genetic variation alters catecholamine secretion and blood pressure. Here effective Chgb protein under-expression was achieved by siRNA in PC12 cells, resulting in ~48% fewer secretory granules on EM, diminished capacity for catecholamine uptake (by ~79%), and a ~73% decline in stores available for nicotinic cholinergic-stimulated secretion. In vivo, loss of Chgb in knockout mice resulted in a ~35% decline in chromaffin granule abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
(92 reference statements)
1
14
0
Order By: Relevance
“…, 2001 ), while CgB is more effective than CgA at inducing secretory granule formation in nonneuroendocrine NIH3T3 and COS-7 cells ( Huh et al. , 2003 ), thus enhancing vesicular storage and the release of catecholamines from PC12 cells ( Zhang et al. , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2001 ), while CgB is more effective than CgA at inducing secretory granule formation in nonneuroendocrine NIH3T3 and COS-7 cells ( Huh et al. , 2003 ), thus enhancing vesicular storage and the release of catecholamines from PC12 cells ( Zhang et al. , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lower CHGB expression level in knockout mice results in fewer catecholamine storage vesicles and unregulated catecholamine release into plasma. 58 Furthermore, expression of granin-related neuropeptides may be further compromised as a side effect of SERPIN protease inhibitor upregulation, potentially restricting release of neuropeptides from their granin precursors. In other words, protease inhibition may protect neurons from inflammation-related apoptosis, but as an unwanted side effect compromise granin processing.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed to participate in forming TGN proteineous aggregates and driving granule biogenesis (Takeuchi and Hosaka, 2008;Tooze, 1998). Studies of CHGB-null mice by two groups reported conflicting results regarding CHGB's role in granule biogenesis (Diaz-Vera et al, 2010; Obermuller et al, 2010;Zhang et al, 2014;Zhang et al, 2009). A mechanistic view on CHGB's intracellular functions is still unavailable.In this work we provide the first elucidation of an important intracellular function of CHGB in the regulated secretory pathway.…”
mentioning
confidence: 99%